Xerostomia appearance in type 1 diabetes mellitus children in RSUPN dr. Cipto Mangunkusumo Jakarta - Puspitasari, Adis Tyaning; Wihardja, Rosiliwati; Runkat, Jakobus (Padjadjaran Journal of Dentistry, 2011)
Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia due to insulin deficiency. As a result, there will be metabolic disturbances on carbohydrate, fat, and protein. Diabetes mellitus type 1 may occur because of pancreatic B cells damage resulting in decreased secretion of insulin in absolute terms. Xerostomia is the medical term for the subjective complaint of dry mouth due to the lack of saliva and can occur in patients with type 1 diabetes mellitus. The purpose of this study was to obtain data on the salivary flow rate and oral dryness complaints in children with type 1 diabetes mellitus The method of this study was descriptive by survey technique. The sample was obtained by purposive sampling and consisted of 30 children with type 1 diabetes mellitus in RSUPN Dr. Cipto Mangunkusumo Jakarta in April to May 2010. The study was conducted with an objective examination by measuring the salivary flow rate and subjective examination using a questionnaire. The results showed that the salivary flow rate from an average of 30 respondents was below normal values. The most common complaints about the dryness of the mouth cavity were thirst, 24 patients (80.00%), and oral dryness 19 patients (63.33%). The conclusion from this study showed that children with type 1 diabetes mellitus were having oral dryness complaints and the decrease of salivary flow rate.